System zarządzania jakością, środowiskiem i bhp w świadomości pracowników - Ejdys, Joanna (Quality, Environmental and Safety Management Systems in Employee's Awareness, 2008)
The paper presents results of the author's research conducted in 5 Polish enterprises among all employees in the field of quality, environmental and safety management systems. The main goals of the research were to find answer for the following questions: 1. How aware are employees of existing in enterprises ISO systems? 2. What kind of benefits of ISO systems do they perceive? 3. What kind of weaknesses of ISO systems do they perceive? 4. Does employees' awareness depend on time of employment, position in company and level of education? (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 391-401